Magnetic field-stimulated change of photovoltage in solar silicon crystals - Korotchenkov, O.O.; Steblenko, L.P.; Podolyan, A.O.; Kalinichenko, D.V.; Tesel’ko, P.O.; Kravchenko, V.M.; Tkach, N.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The effect of static magnetic field (B = 0.17 T) on composition of defects and lifetime of charge carriers in solar silicon crystals has been investigated. Studied in this work was the character of changes in electrical characteristic of solar silicon. These changes are dependent on the time elapsed after the magnetic treatment. The results have been discussed in terms of spin-dependent processes in the subsystem of structural defects.